Microwave transmission line circuits - Joines, William T.; Palmer, W. D.; Bernhard, Jennifer Lyn Truman (Artech House, 2013)
Offers engineers assistance for their work involving microwave circuit analysis and design. This practical book provides a thorough understanding of the properties of planar transmission lines for integrated circuits. It presents matrix and computer-aided methods for analysis and design of circuit components.